The Relationship between Relative Prices and the General Price Level - Vining, Daniel R.; Elwertowski, Thomas C. (American Economic Review, 2016)
It is very nearly a truismi amaong neoclassical economists that the public is wont to confuse changes in the general price level with relative price changes. Correspondingl y, one might speak of the independence between the two as one of the central postulates of the neoclassical tradition. William Stanley Jevons was aml-ong the first to identify this basic dichotomin economic life as well as to attempt to explain the ordinary citizen's seenming incapacity to understand it: